Framework for selecting the best software quality model for a smart health application based on intelligent approach - Ashraf Mousa Saleh; Odai Enaizan (Bulletin of Electrical Engineering and Informatics, 2023)
There is difficulty in knowing how to weigh the factors of software quality models so that decision-making can be eased. Furthermore, previous work was limited to undertake evaluation and selection of appropriate software quality model based upon multi-criteria in the context of smart health applications. This paper aims to evaluate and select an appropriate model of software quality based on multi-criteria decision-making (MCDM) by three phases of framework. Firstly, investigation of software quality models and factors that were identified based on ‘fuzzy delphi’. Secondly, identification of quality models that have uniform multi-criteria so that a decision matrix could be established. Uniform multi-criteria were used in the decision matrix as the basis of the models of quality and the multi-criteria. Subsequently, MCDM approach is adopted and the bases used in the employment of the MCDM approach for the eva luation and selection of the software quality model were technique for order preference by similarity to ideal solution (TOPSIS) and fuzzy analytical hierarchy process (FAHP). The results demonstrated that seven quality factors could be considered as the key factors based upon fuzzy delphi, i.e., usability, maintainability, reliability, interoperability, portability, modifiability, and efficiency. Also, reults shows that McCall is the most appropriate model.